Tanggung Jawab Otoritas Jasa Keuangan (OJK) Provinsi NTB Dalam Mengatasi Permasalahan Investasi Digital Ilegal Yang Merugikan Konsumen Di Lombok (Studi Di PT. FEC Shopping Indonesia) - Una Yukuri, Maelavae; Hirsanuddin (Departement Business Law, Faculty of Law, University of Mataram, 2024)
This research aims to analyze the responsibilities of the NTB Province Financial Services Authority (OJK) in overcoming the problem of illegal digital investment, which is detrimental to Lombok consumers. This type of research is empirical normative legal research. The results of the study show that legal protection arrangements for consumers for losses in making illegal digital investments according to Indonesian laws and regulations are regulated in Law Number 21 of 2011 concerning the Financial Services Authority, Law Number 8 of 1999 concerning Consumers, Law of the Republic Indonesia Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions, Decision of the OJK Board of Commissioners Number: 01/KDK.04/2013 concerning the Investment Alert Task Force and Article 378 of the Criminal Code. The responsibility of the NTB Financial Services Authority (OJK) in dealing with the illegal digital investment case of PT FEC Shopping Indonesia, which is detrimental to consumers in Lombok, is carried out by actively disseminating information that PT FEC Shopping Indonesia is an illegal digital investment through its official social media accounts and providing a means of resolving disputes through the Institution. Alternative Financial Services Sector Dispute Resolution (LAPS SJK).